Implementation of the Revocation Policy for Correctional Clients Who Violate the Special Requirements at Bapas Class I Semarang - Sri Ety Prihartiningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Clients who violate special conditions have not had their social reintegration program revoked. The problem formulation is how to apply the revocation policy to correctional clients who violate the special conditions and the obstacles and solutions in implementing the revocation policy to correctional clients who violate the special conditions. This research was carried out using the Empirical Juridical research method. The research specifications used are analytical descriptive. Data collection uses interviews and document study. From the research carried out, the results are as follows: (1) Revocation of the Social Reintegration Program for Correctional Clients Who Violate Special Requirements at the Semarang Class I Bapas, namely that it is not implemented, causing Correctional Clients to not comply with the rules, which causes discrimination against Correctional Clients who are required to report in an orderly manner, and the obstacles encountered were related to technical implementation and external and internal factors with several solutions